2006
DOI: 10.4049/jimmunol.176.5.2991
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Epigenetic Maintenance of Ly49a Monoallelic Gene Expression

Abstract: Although structurally unrelated, the human killer cell Ig-like (KIR) genes and the rodent lectin-like Ly49 genes serve similar functional roles in NK cells. Moreover, both gene families display variegated, monoallelic expression patterns established at the transcriptional level. DNA methylation has been shown to play an important role in maintenance of expression patterns of KIR genes, which have CpG island promoters. The potential role of DNA methylation in expression of Ly49 genes, which have CpG-poor promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 52 publications
6
42
1
Order By: Relevance
“…The association with combined epigenetic modifications and transcription of NKG2A described in this work are remarkably similar to our results for Ly-49A (21). We have shown previously that both DNA hypomethylation and histone acetylation of an intragenic region are associated with transcriptional activity of Ly-49A.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The association with combined epigenetic modifications and transcription of NKG2A described in this work are remarkably similar to our results for Ly-49A (21). We have shown previously that both DNA hypomethylation and histone acetylation of an intragenic region are associated with transcriptional activity of Ly-49A.…”
Section: Discussionsupporting
confidence: 92%
“…It appears that the whole KIR gene cluster is in an open chromatin conformation with acetylated histones, and expression of individual alleles is associated with hypomethylated clusters of CpG dinucleotides in the promoter region, whereas methylated promoters correlate with lack of expression. Previous work in our laboratory has shown that both DNA hypomethylation and histone acetylation correlate with expression of Ly-49A on ex vivo NK cells (21). In this study, we show for the first time a role for epigenetic mechanisms in regulating expression of NKG2A both in developing and mature adult NK cells.…”
Section: N Atural Killer Cells Play An Important Role In the Immunesupporting
confidence: 63%
See 2 more Smart Citations
“…Genomic DNA was modified with sodium bisulfite as described (29). Converted DNA was used as a template in the following first round of PCR amplifying the MEIS1 promoter region with forward and reverse flanking bisulfite primers.…”
Section: Dna Methylation Analysis Of the Meis1 Promoter Regionmentioning
confidence: 99%